Authentication of electronic evidence in cybercrime cases based on Malaysian laws - Mustapa Sa’di, Mursilalaili; Kamarudin, Abdul Rani; Mohamed, Duryana; Ramlee Saad, Zulfakar (Universiti Putra Malaysia, 2015)
Electronic evidence is one of the many forms of documentary evidence. It is stored and retrievable from electronic devices such as computers and smartphones, particularly in the their hard disks or memory banks. However, due to the fragile nature of electronic evidences, it is prone or susceptible to damage or alteration, as well as destruction due to improper handling or safe keeping. Since it can easily be tampered with or self-deteriorate,establishing the authenticity and reliability of electronic evidence is a technical task. Meanwhile, states of affairs would cause such electronic evidence to be inadmissible or carries low or no weightage whatsoever by the court, thus undermining the prosecution’s or the plaintiff’s case, as the case may be. In order to ensure such evidence is admissible and carry the expected weightage, relevant parties must first prove the authenticity of such evidence and subsequently on its reliability and relevancy. Nevertheless, in cybercrime cases, proving the crime is actually a technical challenge, where the responsible personnel are required to understand what is electronic evidence, how to extract and preserve the originality of such evidence and the laws governing electronic evidence, as well as cybercrimes. This article attempts to explain the scope of electronic evidence in relation to criminal cases such as in cybercrimes, as far as its admissibility and weightage are concerned. The discussion will be based on Malaysian and common laws.